You are here eaudiobook A novel. - Nicholls, David (HarperAudio, 2024)
THE INSTANT #1 SUNDAY TIMES BESTSELLER A Good Housekeeping ""Book We're Most Looking Forward To"" * An Independent Today ""Best Fiction Books to Read"" * A GQ Magazine (UK) ""Best Book of 2024"" * A Harper's Bazaar (UK) ""Best Novels to Read"" * A Daily Record ""Best Novel"" ""Captivating [and] flawless...An affectingly hard-won romance. [Michael is] a sturdy and slyly amusing authority figure, ... flailing amid the debris of a loving marriage gone sour. Marnie is a compulsively witty, winningly cranky near-agoraphobe...Both protagonists are prickly, smart and desperately yearning, but utterly guarded for understandably good reasons. Nicholls builds his own erotic and at times wrenchingly emotional suspense as the would-be lovers reveal past mishaps and surrendered dreams... As in the best romances, we cherish Michael's and Marnie's difficult personalities, and relish the unlikely process that might bring them together. The novel is sharp-tongued and irresistible."" — New York Times Book Review ""I finished this novel in two breathless sittings, as invested in its outcome as I would be in the happiness of a friend. This is the magic of You Are Here: warm, generous and funny, it invites readers into the world of Marnie and Michael with the promise that everyone is welcome, and that choosing happiness and being courageous in any small way we can is always possible. I loved this book."" — Kaliane Bradley, author of The Ministry of Time From the internationally bestselling and Booker Prize-longlisted author of One Day, one of the most enduring love stories of its generation, comes an uplifting and unputdownable love story about second chances. Sometimes you need to get lost to find your way . . . Michael is coming undone. Adrift after his wife's departure, he has begun taking himself on long, solitary walks across the English countryside. Becoming ever more reclusive, he'll do anything to avoid his empty house. Marnie, on the other hand, is stuck. Hiding alone in her London flat, she avoids old friends and any reminders of her rotten, selfish ex-husband. Curled up with a good book, she's battling the long afternoons of a life that feels like it's passing her by. When a persistent mutual friend and some very unpredictable weather conspire to toss Michael and Marnie together on the most epic of ten-day hikes, neither of them can think of anything worse. Until, of course, they discover exactly what they've been looking for. Michael and Marnie are on the precipice of a bright future . . . if they can survive the journey. A hilarious, hopeful, and heartwarming love story—the novel beloved New York Times bestselling author David Nicholls calls "my funniest book yet"—You Are Here is a bittersweet and hopeful story of first encounters, second chances, and finding the way home.